Fabrication of Pineapple Leaf Fibers Reinforced Composites - Cesarino, I. [UNESP]; Carnietto, M. B. [UNESP]; Bronzato, G. R.F. [UNESP]; Leao, A. L. [UNESP] (Springer Nature, 2020)
Consumers are more aware of environmental impacts and climatic problems, which leads to a greater demand for products with technological innovations. Research has the aim to replace and reduce raw materials from fossil sources to renewable sources, such as the natural fibers. Natural fiber composites result from the blending of two materials: one is the plastic and the other a fiber, from agricultural waste in most of the cases. Compared to polymers from fossil sources, this new material has three main advantages: they have an environmental approved; low cost and its physical and mechanical properties are superior. The cultivation of this fruit is large in many tropical countries. After harvesting, the fruit and shoots are removed, and the rest needs to be cut and removed from the soil. This material, most leaves, becomes waste and goes to disposal. However, the use of pineapple leaf fibers as a raw material for natural fiber composites production helps to reduce the pollution caused by these residues and can increase the income of pineapple producers making a channel to new business. To have success in producing NFC, it is necessary to understand process techniques; to the adhesion between fiber and the polymer; the ratio of polymer and natural fiber; and the market (automotive, construction, etc.). But, after reading this chapter, it will be possible to conclude that there is a huge opportunity to improve the natural fibers market in front of the other reinforcements because of their properties.
Keywords: Natural fiber composites; PALF properties; Pineapple fibers; Polymers